Crossing the digital divide - Baker, Glenn (NZ Business, 2010)
Looks at the latest available smart electronic document management systems (EDMS) and print management solutions. Speaks to product managers from Fuji Xerox New Zealand, Konica Minolta Business Solutions NZ, and HP New Zealand about current technology, its capabilities and benefits to businesses, and what to know before implementation. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.